EFFECTS OF INTERNET SHUTDOWN AMONG STUDENTS OF DHANAMANJURI UNIVERSITY - Jibolata Devi, Naorem; Meiringmei, Gaikaongam (International Journal of Research -GRANTHAALAYAH, 2025)
Throughout the world, due to one reason or the another, internet shutdown is going on. It affects to many areas like business, education, health and hygiene and so on. The present paper focus on student’s attitude towards internet shutdown the merit as well as demerit sides. The present article focus on DM university student’s attitude towards internet shutdown.